THE ROLE AND ROLE OF WOMEN SCIENTISTS IN THE DEVELOPMENT OF THE STATE (E Conference Zone, 2022)
The article discusses the role of women in science, their respect and thus ensuring the well-being of society. In general, the attention paid to women scientists in the Republic of Uzbekistan in recent years speaks of reforms in this area.